Siblings with refractory occipital epilepsy showing localized network activity on EEG‐fMRI. (7th January 2013) - Carney, Patrick W.; Harvey, A. Simon; Berkovic, Samuel F.; Jackson, Graeme D.; Scheffer, Ingrid E.
Summary The benign occipital epilepsies of childhood include Panayiotopoulos and Gastaut syndromes; a third syndrome, idiopathic photosensitive occipital epilepsy may also begin in childhood or adolescence. We describe siblings with occipital epilepsy characterized by refractory, frequent, brief visual seizures and normal magnetic resonance imaging (MRI). Electroencephalography (EEG) with functional MRI (fMRI) supports localization of interictal epileptiform activity to the occipital lobes. Our hypothesis is that the siblings share a genetic focal epilepsy arising from a localized occipital network. Although they share many features of Gastaut syndrome, their refractory ongoing seizures in adolescence is unusual and likely due to underlying genetic determinants.